Combinational antitumor strategies of exosomes as drug carriers: Mini review - Xiao, Guixiu; Xu, Zihan; Luo, Feng (Frontiers in Pharmacology, 2023)
Cancer therapies have made tremendous progress in the last decade, but monotherapy still has apparent limitations and lacks therapeutic efficacy. Thus, the simultaneous administration of multiple drugs has been widely explored and has shown better outcomes. Exosomes, deriving from almost all living cells, are natural nanocarriers designed to deliver drugs to tumor sites. Therefore, combinational antitumor therapies based on exosomes, such as engineered exosomes and different combinations of chemotherapeutic agents, therapeutic nucleic acids, photosensitizers, immunotherapy and phytochemicals, have considerable prospects and potential for clinical translation. Here, we summarize current strategies of cancer combination therapy in exosomes and propose opportunities and challenges in the future.